Interface expandida - o vídeo na comunicação on-line - Borovik, Rogério Largman (2005)
Abstract The new conditions provided nowadays by technological advancements have made it possible to develop different ways of videographic production. While granting the concentration of different human activities within a single individual, the processes which are inherent to the digital universe have contributed as completely new tools to communication and collaborative productions. The concept of authorship is being questioned, both in the collective making and in the use of recyclable material, in such a way that a cultural substrate considered banal, every-day stuff and disposable can be transformed into raw material for artistic creation. The main objectives of this study were to present a historical overview of digital video, studying its communication process, enhanced by the arising of the Internet, and to analyze the possibilities inscribed in the audiovisual authoring software Keyworx, that is original both in its conceptual proposal and in its shape, interface and action. Keyworx is not a product manufactured by a company, but rather an educational project of the Waag Society, a Dutch research institution. This software makes a fusion of multi-user teleconference environment aspects with those of digital media process softwares (popularly known as VJ software ). A more profound discussion about the digital video interface and its functioning showed that it is of the utmost importance to a reflection on the particularities of a collaborative video creation model on the net. In this sense, the theories of Edmond Couchot, Lev Manovich, Arlindo Machado, Jay David Bolter, Richard Grusin and Giselle Beiguelman have occupied a key position in this study, because they elucidate aspects of the binary nature of digital media and their implications in the authoring processes, along with interviews with the creators of Keyworx. We could observe that, ever since the beginnings of digital video on the Internet, the communication roles between the sender and the receptor had their definition broadened, converted into interactors of a dialogical communication, which implies changes in the way they are created and distributed in the media.